Ferrocene as a rapid charge regenerator in dye-sensitized solar cells. (September 2016) - El-Zohry, Ahmed M.; Cong, Jiayan; Karlsson, Martin; Kloo, Lars; Zietz, Burkhard
Abstract: Using the reductive power of the ferrocene moiety (Fc), an ultrafast regeneration step via a covalent attachment of a Fc moiety to an organic triphenylamine-based dye (L1) when adsorbed on TiO2 is highlighted. Two modified dyes with one and two Fc moieties attached (L1Fc, and L1Fc2), respectively, were synthesized by addition to the L1 dye. These dyes have been studied spectroscopically using ultrafast transient absorption spectroscopy in the visible and the infrared (IR) regions. In acetonitrile, the results show an ultrafast excited state quenching of the modified dyes due to an expected electron transfer process from the Fc(s) to L1. Adsorbed onto TiO2, an electron transfer process is also detected from Fc to the oxidized dye (L1 + ). Despite the occurrence of an ultrafast regeneration step, the solar cell performance does not improve by the attachment of Fc(s) to the dye L1. Transient absorption measurements in the IR region revealed a fast electron recombination process to the Fc + moiety on an average time scale of ca. 300 ps, outcompeting the >12 ns process to L1 + . The reasons for the observed considerably faster recombination rate to Fc + than to L1 + are discussed in detail. This study provides deep spectroscopic insights for such organic dyes utilized to afford ultrafast regeneration step without showing high performance in photovoltaic devices. In addition, this study will improve our understandings for the triangular relationship between the molecular design, electron kinetics, and the performance in photovoltaic devices. Graphical abstract: Highlights: Ultrafast regeneration step can be accomplished by ferrocene moiety for organic dyes. Ultrafast recombination process to the ferrocene dyes limits the efficiency of the made cells. The combination of different transient absorption techniques is mandatory to uncover different limiting processes.